If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16y + -12 = 0 Reorder the terms: -12 + 16y = 0 Solving -12 + 16y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 16y = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 16y = 0 + 12 16y = 0 + 12 Combine like terms: 0 + 12 = 12 16y = 12 Divide each side by '16'. y = 0.75 Simplifying y = 0.75
| -22=11c(2c+8) | | Y=25-6x | | -7.4x=66.6 | | 1/3+2/3x+3/4=21/12 | | 7(4+k)=42 | | 5y+2=-4+3y | | 5(4x+3)+3(4y+1)=66 | | 3x+3.1=9.4 | | e-24= | | 8x-6=-46 | | -1.5=0.5-2x | | B=ZP | | Y=12x-10 | | Y=12x-10 | | 5(4y+3)+3(4y+1)=66 | | v/w=9 | | h+5=5x(8-3) | | 25=-8x-7 | | 2*(5+3)= | | 2(4+2n)+2(-1n+8)=5n-8 | | 2x(5+3)= | | 6/5k+20=140 | | -8x-14=54 | | 3b+1/2-4=b/3 | | 3x+4x+9=-12 | | y=2/7x-2 | | -x/15x=-1/30 | | -12x-10=80 | | 9=5x-26 | | (4v-2)(6-v)=0 | | 48+(-43)= | | 4y+2(3y+2)=24 |